Second Five Year Plan Revised Proposals of Pondicherry State - Planning Commission (Planning Commission, 1955)
Level of Development estimated up to the end of 1955-56: — the main objective of (he First Five Year Plan was a transformation of the economic system of India so as to secure greater efficiency in production as well as equality of justice. the role of the State in effecting this transformation was to ensure a progressive widening of the public sector and a reorientation of the private sector to the needs of a planned economy. To attain the objective in view, in the First Five Year Plan period, agricultural development received the highest precedence, which necessitated an intensive programme of irrigation covering minor as well as major projects.
Pondicherry State